2012
DOI: 10.3402/fnr.v56i0.11217
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast, midday meals and academic achievement in rural primary schools in Uganda: implications for education and school health policy

Abstract: BackgroundUnderachievement in schools is a global problem and is especially prevalent in developing countries. Indicators of educational performance show that Uganda has done remarkably well on education access-related targets since the introduction of universal primary education in 1997. However, educational outcomes remain disappointing. The absence of school feeding schemes, one of the leading causes of scholastic underachievement, has not been given attention by the Ugandan authorities. Instead, as a natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 13 publications
5
48
2
1
Order By: Relevance
“…Acham et al (2012) demonstrated in well-nourished and undernourished 9-15 year olds predominantly considered low ability, that those who had consumed breakfast and a mid-day meal were almost twice as likely to score highly on achievement tests compared to those who only had one meal. This association was specific to boys, and consuming breakfast alone was not associated with school performance (Acham et al, 2012).…”
Section: Standardized Achievement Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acham et al (2012) demonstrated in well-nourished and undernourished 9-15 year olds predominantly considered low ability, that those who had consumed breakfast and a mid-day meal were almost twice as likely to score highly on achievement tests compared to those who only had one meal. This association was specific to boys, and consuming breakfast alone was not associated with school performance (Acham et al, 2012).…”
Section: Standardized Achievement Testsmentioning
confidence: 99%
“…Acham et al (2012) demonstrated in well-nourished and undernourished 9-15 year olds predominantly considered low ability, that those who had consumed breakfast and a mid-day meal were almost twice as likely to score highly on achievement tests compared to those who only had one meal. This association was specific to boys, and consuming breakfast alone was not associated with school performance (Acham et al, 2012). This gender difference is not consistent across studies with evidence demonstrating increased odds of having lower self-reported school grades when skipping breakfast compared with habitually consuming breakfast in both genders (Lien, 2007).…”
Section: Standardized Achievement Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents and children are still dependants and they need adequate attention and care in order for them to be able to develop meals and food habits that are healthy and will promote good nutritional status (Lazzeri et al, 2013;Nanney et al, 2011;Storey et al, 2011;Wate et al, 2013). Skipping breakfast and unhealthy food consumption may lead to micro nutrients deficiencies and poor nutritional status (Acham et al, 2012;Hallstrom et al, 2013;Pereira et al, 2011;So et al, 2011). The consequences of poor nutritional status at the early stage of life may be so serious that it can result in depression, lack of self esteem, unconsciousness, anxiety, poor cognition and academic achievements and in extreme condition a premature death among school children and used to measure height and weight of participants two adolescents (Acham et al, 2012;Arora et al, 2012; times each and mean height and weight were Bhurtun and Jeewon, 2013;Hoyland et al, 2012;Matthys determined.…”
Section: Introductionmentioning
confidence: 99%
“…Skipping breakfast and unhealthy food consumption may lead to micro nutrients deficiencies and poor nutritional status (Acham et al, 2012;Hallstrom et al, 2013;Pereira et al, 2011;So et al, 2011). The consequences of poor nutritional status at the early stage of life may be so serious that it can result in depression, lack of self esteem, unconsciousness, anxiety, poor cognition and academic achievements and in extreme condition a premature death among school children and used to measure height and weight of participants two adolescents (Acham et al, 2012;Arora et al, 2012; times each and mean height and weight were Bhurtun and Jeewon, 2013;Hoyland et al, 2012;Matthys determined. Two trained professional research et al, 2007;Pereira et al, 2011;Utter et al, 2007).…”
Section: Introductionmentioning
confidence: 99%